Climate change and the changing water cycle: new Indian and UK-India collaborative research initiatives - Remesan, Renji (OMICS International, 2012)
The possible effects of climate change on India’s surface and ground water resources would impart huge pressure on existing water management strategies in coming decades and so. Recent studies shows that the per capita annual water availability in India has considerably reduced from 1820 m3 (2001 statistics) to 1703.6 m3 (2005 statistics) in a limited periods; and this value is very close to the water stress threshold value of 1700 m3 [1]. India is the largest ground water user in world (230 cubic kilometers per year; which is more than quarter of the global total) which covers more than 85% of drinking water supplies and more than 60% of agriculture water are depending on the ground water reserve [2]. As some of the recent studies have highlighted the fact that nearly 29 percent of groundwater blocks in the country fall under the semi-critical, critical, or overexploited categories, the Planning Commission of India has constitute an expert group to identify sustainable management strategies for groundwater use and to provide technical support to enhance outcomes management interventions.